Natural history of bleeding and characteristics of early bleeders among warfarin initiators - a cohort study in Finland - Rikala Maria; Kastarinen Helena; Tiittanen Pekka; Huupponen Risto; Korhonen Maarit Jaana (United Kingdom, 2025)
Aims: The demand for oral anticoagulant therapy will continue to increase in the future along with the aging of the population. This study aimed to determine the rate of bleeding requiring hospitalization and to characterize early bleeders among persons initiating warfarin therapy. Characterization of those most susceptible to early bleeding is important in order to increase the safety of warfarin initiation.
Patients and methods: Using data from nationwide health registers, we identified persons initiating warfarin therapy between January 1, 2009 and June 30, 2012, n = 101,588, and followed them until hospitalization for bleeding, death, or administrative end of the study (December 31, 2012). We defined early bleeders as persons with a bleeding requiring hospitalization within 30 days since warfarin initiation.
Results: The rate of hospitalization for bleeding during a median follow-up of 1.9 years was 2.6% per person-year (95% confidence interval [CI] 2.5%-2.7%), with a peak within the first 30 days of warfarin initiation (6.5% per person-year, 95% CI 6.0%-7.1%). In a multivariable Cox proportional hazards regression analysis, early bleeders were characterized by prior bleeding (<180 days before initiation, hazard ratio [HR] = 13.7, 95% CI 10.9-17.1; during 180 days-7 years before initiation, HR = 1.48, 95% CI 1.15-1.90), male sex (HR = 1.32, 95% CI 1.10-1.57), older age (HR = 1.13, 95% CI 1.04-1.22, per 10-year increase), venous thrombosis (HR = 1.83, 95% CI 1.44-2.34), pulmonary embolism (HR = 1.46, 95% CI 1.11-1.91), alcohol abuse (HR = 1.59, 95% CI 1.08-2.35), rheumatic disease (HR = 1.40, 95% CI 1.07-1.83), and exposure to drugs with dynamic interaction mechanism with warfarin (HR = 1.43, 95% CI 1.20-1.71). In age-adjusted models, Charlson comorbidity index and number of drugs predicted a graded increase in the hazard of early bleeding.
Conclusion: The rate of hospitalizations for bleeding peaked in the beginning of warfarin therapy. Early bleeders were characterized by venous thrombosis, pulmonary embolism, and factors that increase bleeding risk without affecting the international normalized ratio.